The role of organizations in the administration in the Code of Canon Law: the acts of extraordinary administration and alienation of ecclesiastical organizations - INTERGUGLIELMI, ANTONIO (Prawo Kanoniczne, 2013)
The administration of the goods of ecclesiastical organizations is a complex and very delicate task. The practise often shows us how rules of the Code of Canon Law is still partly unclear in order to have a truly effective execution for the protection of institutions assets. In 1983 the CIC on one hand seeks to protect the assets of the institution, giving rules in order to make sure the institution assets: the distinction between acts of extraordinary administration and acts of alienation tries to prevent the assets from suffering an unmotivated decrease. On the other hand, the new code introduces a number of organizations cooperating in the administration, not to leave the administrator without a helping hand. These organisms are first of all to protect those who are responsible for the administration of goods, not only to control their work. This control is accomplished primarily through the authorization canonical acts, intended for all those acts which go beyond the ordinary. However,theseaspectsstill need more completenessin regulation on one hand; on the other hand they need amore effectiveexecution in practice: these twoaspectsare closely linked.